Perancangan Sistem Informasi Penjualan Batik Semarang Berbasis Web Pada Toko Batik Ngesti Pandowo (Information Technology and Telematics, 2016)
Abstract: The Business of Batik Semarang is established in 2011, this effort at the start of manufacture or production (make your own, until a sale). Here not only sell Batik Semarang, but also provides a batik of Solo and Pekalongan. Problems faced is the turnover of fluctuating or fluctuates due to manual sales process is not systematic and less effective and thus require web-based sales. This study aims to determine the extent to which the sales information system at the store BATIK, to evaluate and provide repair system sales information that is held, to propose from web-based sales so as to increase sales turnover and profit, to create a system of new sales and more good. In addition there was a functional purpose to assist consumers in obtaining information fast, accurate and up to date on online shopping in particular regarding products offered information related to product availability, price and quality. System development methods in this study using RAD or Rapid Application Development, a development strategy that prioritizes speed system development through extensive user involvement in the use of a series of construction, where the circuit serves as a model (prototype) system more effective. Based on the analysis and discussion in the previous section, the conclusions of this study are: (1) The design of an online shopping system that offers a variety of features that appeal to customers that shop sales turnover also increased done with the program interesting web. (2) The proposed system can now be used to determine the pattern and the purchasing power of consumers in general so that the process of purchase and sale transactions are becoming more accurate and efficient as well as effective. (3) In making an online sales system become more convenient and practical, especially in terms of search and booking as it is equipped with a variety of menus on consumer data, suppliers, purchases, sales, stock and process the payment method. Keywords: RAD, online shopping system design, sales, web.